1994
DOI: 10.1111/j.1749-6632.1994.tb47391.x
|View full text |Cite
|
Sign up to set email alerts
|

Improved Expression of a Hybrid Streptomyces clavuligerus cefE Gene in Penicillium chrysogenum

Abstract: A hybrid cefE gene, encoding penicillin N expandase, was constructed by fusing the promoter sequences, Pcp, and terminator sequences, Pct from the Penicillium chrysogenum pcbC gene to the open reading frame (orf), cefEorf, from the Streptomyces clavuligerus cefE gene. The resulting hybrid gene, Pcp/cefE'orf/Pct, differed from a previously reported hybrid cefE gene contained on plasmid pPS65. The latter gene, Pcp/cefE'orf/Sct, contained the Pcp sequences fused to the S. clavuligerus cefE orf still attached to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Data are presented as averages 7 mean deviation from at least two independent replicate cultures. Harris et al, 2009b;Queener et al, 1994;Velasco et al, 2000) has transformed this fungus into a platform organism for production of b-lactam antibiotics and their precursors.…”
Section: Metabolic Engineering Of Side-chain Precursor Degradation Inmentioning
confidence: 99%
“…Data are presented as averages 7 mean deviation from at least two independent replicate cultures. Harris et al, 2009b;Queener et al, 1994;Velasco et al, 2000) has transformed this fungus into a platform organism for production of b-lactam antibiotics and their precursors.…”
Section: Metabolic Engineering Of Side-chain Precursor Degradation Inmentioning
confidence: 99%
“…Although recent years have seen few examples of the use of recombinant DNA techniques to improve yields of small‐molecule natural products (14–16), this work showcases the synergy of combining all techniques of process improvement. Mutagenesis techniques have historically been used on the natural producers of polyketides; however, we demonstrated that mutagenesis is also effective on plasmid‐based recombinant organisms.…”
Section: Discussionmentioning
confidence: 97%
“…The secondary structures of residues 81-90 and 167-177 were highly disordered and were not determined [84]. The cylinders, arrows, and black lines represent -helices, -sheets, and coil structures, respectively expression in E. coli [28,34,49], S. lividans [22,33], Penicillium chrysogenum [13,24,68,[70][71][72][73], Pseudomonas putida [47], and Pichia pastoris [3]. High level expression of recombinant scDAOCS has often been carried out in E. coli cells together with the use of traditional extraction to purify scDAOCS from E. coli cell lysate for biochemical studies [57,58,90].…”
Section: Expression Of Recombinant S Clavuligerus Daocsmentioning
confidence: 99%